Identifikasi Problem Usaha Mikro Pada Pengrajin Sangkar Burung Kadilangon Di Masa Covid-19 - Rustam Hanafi; Sutapa (Universitas Lancang Kuning, 2022)
The birdcage craftsman center in the hamlet of Kadilangon, Kebonbator, has occurred hereditary for three generations, but they have not shown significant prosperity. Therefore, this community service aims to identify the problems faced by partners until to provide solutions and assistance through continuous service. It was done by interviewing partners with door-to-door representation. Because, first, there were strict restrictions on mass gatherings during the COVID-19. Second, partners are less familiar with smartphones, so difficult for online. With this method, we can explore in depth the main problems faced by partners. This community service finds that partners have basic problems for developing. First, they generally have an employee mindset, not an entrepreneur mindset. Second, they cannot access funding because of limited information and knowledge. The solutions offered for the next service are entrepreneurship training and the formation of savings and loan cooperatives and production as facilitation of partner business development.